States, Intergovernmental Relations, and Market Development - Cheng, Jinhua. author. aut Link
XVII, 233 p. 3 illus.
Keywords: This book is a theoretical and empirical analysis of institutional foundation of long-term economic growth from the perspective of state-market and central-local relations. The book argues that, in order to safeguard sustainable market development, it is necessary to centralize certain functions of the state to overcome local predatory governmental rulings, and to decentralize others to increase local governmental market incentives, simultaneously. This institutional approach is conceptualized as “Dual Intergovernmental Transformation for Market Development” (DITMD). This book develops the DITMD model through an in-depth empirical comparison on contemporary China and the 19th-century United States. Jinhua Cheng is Distinguished Professor of Law at Shanghai Jiao Tong University KoGuan School of Law and Executive Director of the Law and Society Center. His research focuses on comparative central-local relations, empirical legal studies, law and financial development, lawyers and society. Professor Cheng received his Bachelor of Laws from East China University of Political Science & Law in 1998, Master of Laws from Peking University in 2001, M.Phil. in Social Science from Hong Kong University of Science & Technology in 2005, and L.L.M., and J.S.D. from Yale University in 2007 and 2011 respectively.